2007
DOI: 10.1002/mop.22706
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of wave digital model in analysis of arbitrary nonuniform transmission lines

Abstract: An efficient method of analysis of nonuniform transmission lines (NTL), based on wave digital model composed of cascaded unit elements and two‐port adaptors, is described. The proposed technique treats NTL as a cascade connection of equal‐length or equal‐delay uniform transmission lines. A simple algorithm for calculating transmission and input reflection coefficients is derived. Two application examples, proving the efficiency and response accuracy of the new technique, are given. © 2007 Wiley Periodicals, In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 6 publications
3
4
0
Order By: Relevance
“…The simulation result of scattering parameter 21 S is depicted in Figure 8. When compared with the findings of the previous studies [5][6][7], the computer simulated result is found to be consistent with them.…”
Section: B Proposed Algorithmsupporting
confidence: 78%
See 3 more Smart Citations
“…The simulation result of scattering parameter 21 S is depicted in Figure 8. When compared with the findings of the previous studies [5][6][7], the computer simulated result is found to be consistent with them.…”
Section: B Proposed Algorithmsupporting
confidence: 78%
“…A computer program is written to implement the proposed algorithm, and one test case is performed: a microstrip lowpass filter [6]. The result is found to be consistent with the findings of the previous studies [5][6][7].…”
Section: Introductionsupporting
confidence: 77%
See 2 more Smart Citations
“…Finally, WDN pictured in Figure 2, designed as a cascade connection of frequency-independent twoport series adaptors and a frequency-dependent twoport UEs is obtained. Analysis of resultant network is then done using earlier developed one-dimensional wave digital approach [4]. 978-1-4673-5707-4/13/$31.00 ©2013 IEEE…”
Section: B1mentioning
confidence: 99%